2012
DOI: 10.1016/j.jamcollsurg.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hazardous Drinking Behavior in 1,340 Adult Trauma Patients: A Computerized Alcohol Screening and Intervention Study

Abstract: BACKGROUND: Alcohol screening and brief intervention (SBI) is used to decrease alcohol consumption, health care costs, and injury recidivism in trauma patients. Despite SBI being mandated for trauma centers, various concerns have led many centers to conduct SBI only on patients with a detectable blood alcohol concentration (BAC). We sought to determine the predictive nature of BAC on hazardous drinking behavior. STUDY DESIGN: Adult trauma patients were included if they received an SBI before discharge. SBI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Specific tablet-based (not laptop or desktop computer) screening for harmful alcohol and drug use in the ED has been previously described, and these studies have some differences and similarities to our findings. A 2012 study of tablet Computerized Alcohol Screening and brief Intervention (CASI) of trauma patients using AUDIT was one of the first to describe the use of tablets in the ED to determine predictive factors for “hazardous drinking behavior” [ 37 ]. However, no mention was made of time to completion, proportion of patients who refused, or details of the tablet-based brief intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Specific tablet-based (not laptop or desktop computer) screening for harmful alcohol and drug use in the ED has been previously described, and these studies have some differences and similarities to our findings. A 2012 study of tablet Computerized Alcohol Screening and brief Intervention (CASI) of trauma patients using AUDIT was one of the first to describe the use of tablets in the ED to determine predictive factors for “hazardous drinking behavior” [ 37 ]. However, no mention was made of time to completion, proportion of patients who refused, or details of the tablet-based brief intervention.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Ewing et al administered the computerized alcohol screening and intervention (CASI) system to screen over 1,000 traumatized patients for alcohol use with the aforementioned AUDIT tool in electronic format. 24 And although not for screening purposes, an interactive computerized history-taking program has been successfully used to augment history information at triage without delaying patient care. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Gender is also significantly associated with alcohol consumption 38,39) . Our results revealed that 34% of women drank alcohol compared with 50% of men and that 8% of the women and 16% of men could be considered hazardous drinkers.…”
Section: Discussionmentioning
confidence: 98%